Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
(0, -3)
Step-by-step explanation:
y = 3x - 3
y = x - 3
In the solution to the system of equations, y is the same number for both of those functions. So 3x - 3 = x - 3.
Then solve for x:
3x - 3 = x - 3
Add 3 to both sides
3x = x
Subtract x from both sides
2x = 0
Divide both sides by 2
x = 0
Now that you have x, substitute it in one of the equations:
y = 3x - 3
y = 3(0) - 3
y = -3
x is 0 and y is -3, so the solution to the equation is (0, -3)
Answer:
x = 0
Step-by-step explanation:
y=3x-3
y=x-3
They both equal why so you can take away the y and put them equal to each other.
3x-3=x-3
Subtract x from both sides
2x-3=-3
Add 3 to both sides
2x=0
divide 2 from both sides
x=0
The answer is 0. Hope this helps you :)
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.